Efficiency of application the solidification/stabilization technique on mine tailings from the Bor - Dunja Rađenović; Miladin Gligorić; Stefan Đorđievski (Zaštita Materijala)
Disposal of mine tailings which appears during the mining activity from Bor mine, represents enormously large environmental problem, because mine tailings is highly polluted by heavy metal, in this case by copper. Therefore it is necessary to expose mine talling s to certain treatments of remediation. In this work main object of the study was to show the leaching of metals and treatment efficiency of mine tailings from Bor that was stabilized/solidified by applying clay and fly ash as an immobilization agents. Cha racterization was preformed using semi-dynamic leaching test ANS 16.1. All immobilization agents in the treatment of copper were quite successful in the stabilization/solidification of mine tailings. Treated waste can be considered acceptable for disposal, and even considered for 'controlled utilization'.